Tradable permits to manage urban mobility: market design and experimental implementation - Devi Brands; Erik T. Verhoef; Jasper Knockaert; Paul Koster (Tinbergen Institute, 2019)
Congestion levels have grown substantially in recent years, while the traditional economic response to congestion – road pricing – remains politically infeasible in most locations. Tradable permits are likely to be a more viable alternative, because they do not require a net financial flow from road users to the government. It is therefore the right moment to design and empirically test tradable permit schemes for managing urban mobility. This paper presents and empirically tests a complete design of a market for tradable permits, both in terms of the conceptual set-up of the market as well as its technical implementation. The design is evaluated against a number of criteria, including: transparency and containment of transaction costs, stability of permit prices in relation to the dynamic equilibrium on the mobility market and the prevention of undesirable speculation and fraud. We present evidence of the empirical functioning of this market, using the results of a conducted lab-in-the-field experiment with virtual mobility behaviour and real financial incentives.
Keywords: R41; R48; H23; Q58; 330; Mobility credits; Tradable credits scheme; Permit experiment; Permit market